Effects of L-/N-Type Calcium Channel Blockers on Angiotensin II–Renin Feedback in Hypertensive Patients. (22nd December 2020) - Kawabata, Yutaka; Soeki, Takeshi; Ito, Hiroyuki; Matsuura, Tomomi; Kusunose, Kenya; Ise, Takayuki; Yamaguchi, Koji; Tobiume, Takeshi; Yagi, Shusuke; Fukuda, Daiju; Yamada, Hirotsugu; Wakatsuki, Tetsuzo; et al.
Abstract : Objectives . Cilnidipine, an L-/N-type calcium channel blocker (CCB), has unique organ-protective properties due to suppression of hyperactivity in the sympathetic nervous system and renin-angiotensin system (RAS). In this study, we hypothesized that cilnidipine might exert a renoprotective effect by suppressing the RAS. Methods . A total of 25 hypertensive patients receiving a RAS inhibitor were randomly assigned to a cilnidipine ( n  = 12) or amlodipine ( n  = 13) group. The effects of cilnidipine on proteinuria and angiotensin II–renin feedback were assessed. Results . After 6 months of treatment, both systolic and diastolic blood pressures were significantly reduced to a similar extent in both groups. The urine albumin-to-creatinine ratio was significantly lower in the cilnidipine group (p < 0.05 ) than in the amlodipine group. Amlodipine increased plasma angiotensin I and angiotensin II levels (p < 0.05 ), whereas cilnidipine did not. Interestingly, the cilnidipine group had a higher ratio of angiotensin-(1–7) (Ang-(1–7)) to angiotensin II in plasma than the amlodipine group (p < 0.05 ). Conclusions . The L-/N-type CCB cilnidipine, but not amlodipine, decreased urinary albumin excretion in hypertensive patients. Cilnidipine also increased the ratio of Ang-(1–7) to angiotensin II in plasma, which might be one factor underlying its beneficial effects.